Clinical Predictors of Response to Treatment with Tofacitinib (Janus Kinase Inhibitor) in Patients with Ankylosing Spondylitis - Bukhari , Syeda Kinza; Khan , Javed Ahmad; Hashmi , Zoha; Bushra; Sheen , Irfan Najam; Akram , Ishwah (Indus Journal of Bioscience Research, 2025)
Objective: To evaluate the efficacy of tofacitinib in ankylosing spondylitis patients and determine the factors predicting treatment outcomes. Study Design: Quasi-experimental study. Duration and Place of Study: The study was conducted from January 2024 to November 2024 at the Department of Medicine, Combined Military Hospital (CMH), Multan. Methodology: A total of 169 patients, aged ≥18 years, with active ankylosing spondylitis fulfilling the modified New York (mNY) criteria, were enrolled through non-probability consecutive sampling. Patients with CRP values within reference range, active arthritis, and concurrent therapy with methotrexate or stable prednisone were included. All participants received 5 mg twice daily of tofacitinib for 12 weeks, followed by a 4-week washout period. The primary efficacy outcome was assessed using the ASAS20 criteria at week 12. Factors predicting treatment outcomes were also analyzed. Results: Out of 169 patients, 68% achieved an ASAS20 response after 12 weeks of tofacitinib, with a mean reduction in CRP of 35%. Higher response rates were seen in patients with moderate to severe disease (82%) and those with elevated baseline CRP (>10 mg/L, 76%). Obesity (BMI ≥30 kg/m²) and IBD were associated with lower efficacy (62% and 59%, respectively). CVD had no significant impact on treatment outcomes (68% response). Conclusion: Tofacitinib demonstrates significant therapeutic efficacy in AS patients, with baseline disease activity and elevated CRP being strong predictors of a positive treatment outcome.